Methamphetamine abuse in Malaysia: a narrative review of epidemiology, health consequences, and intervention strategies - Jaffer, Usman; Abduallah, Nur Haizatul Ain; Achmad, Rozlina; Rosli, Nurfahana; Shahrolidham, Nuradeena Safia; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Ahmad H.Osman, Rahmah (Global Academic Excellence, 2024)
Methamphetamine abuse remains a pressing global public health challenge, with many countries—including Malaysia—continuing to grapple with its multifaceted social and economic repercussions. Despite the implementation of rigorous drug control policies and extensive rehabilitation programmes, methamphetamine addiction continues to pose significant risks to individuals, families, and the broader community. This narrative review synthesises contemporary evidence on methamphetamine misuse in Malaysia by drawing on a range of studies from local and international sources. The review addresses the epidemiological patterns of use, discusses the psychosocial and neurobiological mechanisms underlying methamphetamine addiction, and highlights the detrimental health impacts linked to chronic use. Special attention is directed towards behavioural and pharmacological intervention strategies, including the current status of pharmacotherapy research for methamphetamine use disorder (MUD). While non-pharmacological methods—such as cognitive-behavioural therapy and contingency management—have demonstrated varying degrees of efficacy, the limited progress in pharmacological options underscores the complexity of treating methamphetamine addiction. By consolidating insights from existing research, the review aims to inform policy-makers, healthcare professionals, and community stakeholders of the urgency to develop evidence-based, tailored solutions that address the dynamic needs of individuals who misuse methamphetamine in Malaysia.